Jenis, Makna, dan Fungsi Interjeksi 아 (a) pada Drama Korea Twenty-Five Twenty-One (스물다섯 스물하나) - Dilla, Mega Khasna; Wahyuningsih, Sri (East Asian Review, 2025)
Interjection is a fundamental aspect of everyday communication and can also be observed in literary works, such as drama. This article examined the Korean interjection 아 [a] and its functions as discourse markers in the Korean drama ‘Twenty-Five Twenty-One’. This study employed the theoretical frameworks of interjections as outlined by Nam et al. (2019) and discourse markers as delineated by Jeon (2002). The findings of this study indicated that the interjection ‘아’ [a] could be classified into three distinct categories: (1) emotive interjections, (2) volitive interjections, and (3) speech habit and stuttering interjections. Among these categories, the speech habit and stuttering interjections, which convey meanings to speech habit, were found to be the most prevalent. In its function as a discourse marker, the interjection 아 [a] was found to have three categories: (1) topic and topic cohesion, (2) topic and speaker cohesion, and (3) speaker and listener cohesion. Of these categories, the topic and speaker cohesion type, which functions to express negative attitudes, were found to be the most prevalent.